The Effect of Constructivist Learning Model for Teaching Biology in Developing the Scientific Thinking of Year Four Female Students - Hashim al-Jameel, Ghadah (Journal of Duhok University, 2019)
The present research aims at identifying the effect of constructivist learning model to teaching biology in developing the scientific thinking of fourth female students . So the researcher has put two null hypotheses , the first supposed no existence of statistic difference between the experimental group which is taught by constructivist learning model and control that is taught by the normal method in scientific thinking. The second hypothesis supposes no existence of statistic difference between the experimental and control groups in developmental means of scientific thinking . The sample consist of (74) female students chosen from fourth class female students for the academic year 2007/2008, which was divided to two equal groups . The experimental group whose number is (36) female taught by using constructivist learning model , where the control group is having (38) female students . The researcher has depended on scientific thinking strategies test prepared by (Al-Abage, 2005) after define its validity and reliability to measure scientific thinking variable . After the experiment and data analyze the results showed statistical differences between the experimental and control group in scientific thinking . They have also reveled difference between the experimental and control group in developmental means of scientific thinking on the behalf experimental group which taught by constructivist learning model .